Ranaviruses Lethal Pathogens of Ectothermic Vertebrates - Gray, Matthew J.; Chinchar, V. Gregory (Springer Nature, 2015)
Animal Ecology; Environmental Health; Fish & Wildlife Biology & Management; Virology; Freshwater & Marine Ecology; Conservation Biology/Ecology